Enantioselective Construction of Spirooxindole‐Fused Cyclopenta[c]chromen‐4‐ones Bearing Five Contiguous Stereocenters via a Stepwise (3+2) Cycloaddition. Issue 8 (23rd March 2020) - Vagh, Sandip Sambhaji; Karanam, Praneeth; Liao, Cheng‐Chieh; Lin, Ting‐Han; Liou, Yan‐Cheng; Edukondalu, Athukuri; Chen, Yi‐Ru; Lin, Wenwei
Abstract: The bifunctional quinine‐catalyzed stepwise (3+2) cycloaddition for the enantioselective construction of spirooxindole‐fused cyclopenta[ c ]chromen‐4‐ones is developed. The reactions of 3‐homoacylcoumarins and alkylidene oxindole electrophiles generate aforementioned spirooxindole‐chromenone adducts bearing five contiguous stereocenters, of which one is the spiro all‐carbon quaternary stereocenter in high yields (up to 99%) with excellent stereoselectivities (up to >20:1 dr and 99% ee). This methodology was investigated for three different alkylidene oxindole electrophiles and could also be practically demonstrated on a gram scale. Mechanistic investigations revealed that the (3+2) cycloaddition for the enantioselective synthesis of spirooxindole‐fused cyclopenta[ c ]chromen‐4‐ones is proceeding via a stepwise reaction pathway. Abstract :